Food is medicine intervention shows promise for engaging patients attending a safety-net hospital in the Southeast United States - Owens, Caroline; Cook, Miranda; Goetz, Joy; Marshburn, Leslie; Taylor, Kathy; Schmidt, Stacie; Bussey-Jones, Jada; Chakkalakal, Rosette J. (Frontiers in Public Health, 2023)
Public health organizations, including the Academy of Nutrition and Dietetics and the American Hospital Association, recognize the importance of achieving food and nutrition security to improve health outcomes, reduce healthcare costs, and advance health equity. In response, federal, state, and private agencies are increasingly seeking to fund healthcare-based interventions to address food insecurity among patients. Simultaneously, nutrition-based interventions targeting chronic diseases have grown across the United States as part of the broader “Food is Medicine” movement. Few studies have examined the successes, challenges, and limitations of such efforts. As Food is Medicine programs continue to expand, identifying common approaches, metrics, and outcomes will be imperative for ensuring program success, replicability, and sustainability. Beginning in 2020, the Food as Medicine (FAM) program, a multipronged, collaborative intervention at Grady Health System has sought to combat food insecurity and improve patient health by leveraging community resources, expertise, and existing partnerships. Using this program as a case study, we (1) outline the collaborative development of the FAM program; (2) describe and characterize patient engagement in the initial 2 years; and (3) summarize strengths and lessons learned for future hospital-based food and nutrition programming. As this case study illustrates, the Food as Medicine program provides a novel model for building health equity through food within healthcare organizations.